2019
DOI: 10.3390/ijms20030709
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: A Small Molecule but Important for Salt Stress Tolerance in Plants

Abstract: Salt stress is one of the most serious limiting factors in worldwide agricultural production, resulting in huge annual yield loss. Since 1995, melatonin (N-acetyl-5-methoxytryptamine)—an ancient multi-functional molecule in eukaryotes and prokaryotes—has been extensively validated as a regulator of plant growth and development, as well as various stress responses, especially its crucial role in plant salt tolerance. Salt stress and exogenous melatonin lead to an increase in endogenous melatonin levels, partly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(121 citation statements)
references
References 117 publications
5
116
0
Order By: Relevance
“…The salt stress damage to plants is mainly manifested through osmotic stress, ion stress, and antioxidant system and hormone signal transduction, among other phenomena [35,7]. Various osmotic regulatory substances can be actively accumulated in plants, allowing them to cope with damaged cells and maintain homeostasis between the internal and external environments of cells, thus enabling plants to slowly adapt to salt stress [23]. A similar pattern is observed in salt-stress seeds, but with reduced growth rates and germination rates, indicating salt stress affects germination of cotton seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salt stress damage to plants is mainly manifested through osmotic stress, ion stress, and antioxidant system and hormone signal transduction, among other phenomena [35,7]. Various osmotic regulatory substances can be actively accumulated in plants, allowing them to cope with damaged cells and maintain homeostasis between the internal and external environments of cells, thus enabling plants to slowly adapt to salt stress [23]. A similar pattern is observed in salt-stress seeds, but with reduced growth rates and germination rates, indicating salt stress affects germination of cotton seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate application of melatonin has been shown to promote not only soluble protein content in Malus hupehensis but also the accumulation of soluble sugar in kiwifruit leaves, while increasing cell fluid concentrations and resistance to stress [21,22]. Under salt stress, accumulation of Na + under salt stress of plants leads to ion imbalances and toxicity, with K + content decreasing as exogenous melatonin promotes the absorption of K + , suggesting that melatonin can regulate ion homeostasis or gene expression responses under salt stress to mitigate damage caused by stress [23][24][25][26].…”
mentioning
confidence: 99%
“…Salt stress is one of the most commonly encountered abiotic stresses for plants, and soil salinization is a severe environmental problem affecting crop fields. The current research provides insight into melatonin applications enhancing salt tolerance in various crop species [50,51]. Alfalfa is one of the most important forage grasses cultivated worldwide with a high biomass yield and a high protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress strongly limits the growth, quality and productivity of alfalfa [6]. Melatonin is an environmentally friendly bioactive molecule, which plays important roles in plant defense against salt stress [50]. Previous reports have confirmed that exogenous melatonin promoted alfalfa drought tolerance by modulating nitro-oxidative homeostasis and proline metabolism [43] and promoted waterlogging tolerance by regulating polyamine and ethylene metabolism [48].…”
Section: Discussionmentioning
confidence: 99%
“…This finding has created new expectations for melatonin's function as a plant hormone [49]. Although this important discovery has elucidated the upstream pathway regarding stomata closure phenotype, there is still the need to explore the crucial role of other melatonin receptor-mediated signaling pathways during biotic/abiotic stress in plants [25,76], although interesting transcriptome approaches have already been made [41]. Recent studies that discerned the ability of melatonin to upregulate ETI and PTI defense-related genes need to affirm their findings within proteomic approaches by establishing a clear signal transduction pathway for this process.…”
Section: Conclusion and Research Gapsmentioning
confidence: 99%